FEASIBILITY OF IDENTIFY (TM) OPTICAL SURFACE GUIDANCE SYSTEM FOR CRANIOSPINAL IRRADIATION - MacLennan, Ranslee; Ploquin, Nicolas; Murtha, Nathan (Radiotherapy and oncology, 2025)
Purpose:Craniospinal irradiation (CSI) at our centre is delivered using a multi-isocentric technique. For CSI, patient alignment at each isocentre is verified using orthogonal kV imaging to ensure adherence to procedural tolerances. A retrospective review of the first three fractions from 20 adult CSI treatments between 2019 and 2024 was conducted to assess the time allocation for patient alignment and treatment. On average, kV imaging accounted for 34% of the total treatment time, representing a substantial portion of the overall patient appointment duration. This study seeks to determine whether the Varian IDENTIFY TM surface guidance system can be used in place of kV orthogonal imaging for the initial alignment of CSI patients. We propose that a surface guidance system can improve CSI patient experience by reducing the alignment time while maintaining or improving alignment accuracy. Materials and Methods:The IDENTIFY TM system uses three cameras to generate a real-time surface contour of the patient. This real-time contour is continuously compared to a predefined reference contour, enabling the system to detect and quantify translational and rotational deviations. By providing precise positional data, IDENTIFY TM enables accurate patient alignment. Unique regions of interest (ROIs) are defined on the body contour at each isocentre. A prospective study was conducted using an anthropomorphic phantom to compare positioning accuracy between the IDENTIFY TM system and kV imaging. A CT scan was acquired of the phantom immobilized with an open-face five-point shell. Next, a surface contour of the phantom was generated, and a treatment plan consisting of three isocentres was created. ROIs were defined at each isocentre, selecting areas with stable, prominent anatomical features to minimize susceptibility to rapid contour changes in a clinical setting. A series of measurements were performed for each isocentre in which the phantom was initially aligned based on IDENTIFY TM-derived positioning data, followed by orthogonal kV imaging for setup verification. Results:Across all isocentres, the largest difference between IDENTIFY TM and kV imaging registrations was 0.07cm in translational shifts and 0.4 degrees in rotational adjustments. The positioning data from the phantom study shows a high level of agreement between IDENTIFY TM and kV imaging, remaining well within institutional tolerances for each isocentre. Conclusions:This study suggests that the current patient alignment procedure based on kV imaging can be substituted with the IDENTIFY TM system without compromising accuracy.